ANALISIS SIFAT KIMIA GAMBUT PASCA KEBAKARAN DENGAN BERBAGAI UPAYA PEMULIHAN HUTAN DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) TUMBANG NUSA, KALIMANTAN TENGAH - Fytria Kurniasari; Syahrul Kurniawan; Lenny Sri Nopriani; Dony Rachmanadi (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Peat land has an important role, function, and benefit for human life, biodiversity, and global climate. The peat swamp forest in Central Kalimantan was devastated to a very large extent, which addresses the restoration of peat swamp forests, has changed the characteristics of peat which contain physical, chemical, and biological characteristics. Peat recovery efforts carried out at the KHDTK Tumbang Nusa consist of natural succession and revegetation. The study aimed to analyze the chemical properties of peat soils in different types of post-fire forest protection and to assess the spatial variability of peat chemical properties in Forest Areas for Special Purposes (KHDTK) Tumbang Nusa, Desa Tumbang Nusa, Jabiren Raya District, Pulang Pisau Regency. The research plot consisted of forest restoration efforts, namely secondary forest, revegetation, and natural regeneration. Variable measured consisted of pH, total organic C, CEC, N, P, K, exchangeable K, Na, Ca, Mg, as well as ash content and water content. The results showed that secondary forest treatment was the best peat swamp forest restoration technique. Spatial variability sub-plots and sample points did not significantly affect the differences in chemical properties of the peat, but the differences in chemical properties of peat is the peat swamp forest was determined by restoration technique.